Late Quaternary glacier advances in the Andes of Santiago, central Chile, and paleoclimatic implications - Herrera-Ossandón, Mariajosé; Easton, Gabriel; Antinao, José Luis; Forman, Steven L. (Frontiers in Earth Science, 2023)
Andean mountain glaciers in central Chile are in a transitional zone between the seasonal influence of the mid latitude westerlies and subtropical semiarid conditions to the north. Long-term glacial dynamics for these glaciers and its relationship with paleoclimate during the Late Quaternary are poorly known despite their relevancy. We estimate here the timing and extent of late Pleistocene-early Holocene glaciers in the Andes of Santiago (33º50’S) from geomorphological and geochronological analyses. Our observations evidence a glacial stage occurred before the Last Glacial Maximum (ELGM) at San Gabriel drift (1300 m a.s.l.), dated as 46-36 ka. Glacial stages during the latest Pleistocene-early Holocene transition period, partially concomitant with the Antarctic Cold Reversal (ACR) and with the Younger Dryas (YD) chronozones, were identified and dated at La Engorda drift (2450-2570 m a.s.l.), at 15-10 ka. We propose that San Gabriel drift represents a prolonged glacial advance driven by increased precipitation and cold sea surface temperatures (SSTs) off central Chile during glacial times. In La Engorda drift, late glacial advances occurred associated with increased regional precipitation, in the context of a climate transition from humid to arid conditions in central Chile, concomitantly with a general warming trend of SSTs offshore in the southeastern Pacific and with reduced austral summer insolation. The results support the sensitivity of Andean mountain glaciers to precipitation and paleoclimate conditions most possibly associated with periods of increased northward influence of mid latitude westerlies during glacial and late glacial times, in addition to El Niño/Southern Oscillation (ENSO) impact since the mid Holocene, driving Late Quaternary glacier advances in central Chile. We estimate a maximum variation of 1200 m in the position of the Late Quaternary Equilibrium Line Altitude (ELA), inferred at 3400 and 3600 m a.s.l. at the time of San Gabriel and La Engorda drifts, respectively, with respect to its modern location close to 4600 m a.s.l.